Why is China Growing So Fast? - Khan, Mohsin (Economic Issues; Economic Issues ;, 1997)
Since 1978 the Chinese economy has grown on average more than 9 percent a year. Per capita income has nearly quadrupled in the past 15 years and some analysts predict that within 20 years the Chinese economy will be larger than that of the United States. This pamphlet analyzes the reasons for the extraordinary growth of the Chinese economy.